Research on the Effects of COVID-19 on Guangdong Province Agricultural Products Export and Countermeasures Under Digital Trade - Xiaomei Li (Law and Economy, 2022)
Abstract: With the outbreak of Corona Virus Disease 2019 (hereinafter referred to as COVID-19) in Wuhan starting in 2020 spreading worldwide, domestic and foreign trade in all walks of life in all countries in the world has been affected to varying degrees. In many industries, COVID-19 has brought greater impact and challenges to agricultural trade. Guangdong Province is China’s leading agricultural export destination, which has suffered the greatest resistance to development under the influence of COVID-19. However, with the rapid development of digital trade, the foreign trade of agricultural products in Guangdong Province has ushered in a “spring”. Therefore, under digital trade, this paper analyzes the challenges faced by Guangdong’s agricultural exports due to COVID-19, and puts forward effective countermeasures to help the steady progress of the province’s agricultural foreign trade.